Homogeneous peptide-break assay for luminescent detection of enzymatic protein post-translational modification activity utilizing charged peptides - Kopra K.; Tong-Ochoa N.; Laine M.; Eskonen V.; Koskinen P.; Härmä H. (Elsevier B.V., 2022)
We have developed a rapid and sensitive universal peptide-based time-resolved luminescence assay for detection of enzymatic post-translational modifications (PTMs). PTMs play essential roles in intracellular signaling and cell regulation, thus providing functional protein diversity in cell. Due this, impaired PTM patterns have been linked to multiple disease states. Clear link between PTMs and pathological conditions have also driven assay development further, but still today most of the methodologies are based on single-specificity or group-specific PTM-recognition. We have previously introduced leuzine-zipper based peptide-break technology as a viable option for universal PTM detection. Here, we introduce peptide-break technology utilizing single-label homogeneous quenching resonance energy transfer (QRET) and charge-based peptide-peptide interaction. We demonstrate the functionality of the new assay concept in phosphorylation, deacetylation, and citrullination. In a comparable study between previously introduced leucine-zipper and the novel charge-based approach, we found equal PTM detection performance and sensitivity, but the peptide design for new targets is simplified with the charged peptides. The new concept allows the use of short <20 amino acid peptides without limitations rising from the leucine-zipper coiled-coil structure. Introduced methodology enables wash-free PTM detection in a 384-well plate format, using low nanomolar enzyme concentrations. Potentially, the peptide-break technique using charged peptides may be applicable for natural peptide sequences directly obtained from the target protein.